A reformulação globalizada do espaço e da violência na Palestina: o mecanismo politico global-local dos Acordos de Oslo - Pacheco, Arturo Benito Hartmann (2020)
The present research aims to understand how state and non-state actors involved in the peacebuilding process in Palestine ended up interlocking themselves in the dynamics of the local colonial confrontation. The study’s objective is to insert itself in the more recent debates about the impact of the Oslo Accords, after almost 30 years of its signature, over the political possibilities in what we know as the Palestinian question. That was made, in a first step, with the analysis of the historical picture of the dynamics of space and violence of the local confrontation, together with the first attempts to advance a peace process, in the 1970 and 1980s. After that, we traced different key moments of the present process through the analysis of documents and political dynamics that framed the involvement of local and global agents. Finally, through the observation of the junction of neoliberal economic policies and more recent Israeli military actions, we were able to observe the dynamics of fragmentation of the territories of the Gaza Strip, Ramallah, and Jordan Valley, capturing the role of the international community in the reformulation of space and violence in the colonial confrontation in Palestine. This way, we could conclude that, in the configuration acquired in the specific case observed, the more broad intervention distorted into a political mechanism producing a geography of disaster. The research aims to open reflections about dilemmas and possibilities of conflict resolution in the current global order